Angiotensin II type 1 receptor (AGTR1) methylation is inversely associated with HbA1c level in non-diabetic young adults - Wan Omar, Wan Fatein Nabeila; A.Talib, Norlelawati; Mohd. Shah, Aida Nur Sharini; Mohd Shah, Azarisman Shah; Abdullah, Aszrin (2019)
Introduction: The increasing incidence of early onset type 2 diabetes worldwide is worrying. Epigenetics may play a role in the pathophysiology of insulin resistance and glucose intolerance. It is hypothesized that overexpression of angiotensin II type 1 receptor (AGTR1) in pancreas impairs insulin sensitivity and insulin secretion, explaining the improved glycaemic control in diabetic patients on angiotensin receptor blocker. Methylation changes in pancreas may be parallel with peripheral blood. To date, the association between AGTR1 methylation and glycemic control has never been investigated. Therefore, the aim of this study is to investigate the association between AGTR1 promoter methylation level and glycaemic control parameters in non-diabetic young adults.